(3QSGdI GdRhQGAs - (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3CeG HYOagPg fHPg ef GMbGFb Hd RHOI ef GdObGFb eHfjI Yf JTHjgGJ eHfjI Ydi JfHjgGJ s
(3BNQgG (B:s
(3hCTQcfj aj UhGdM OYhGJc hGdUdGg hGdSdGe Ydi GdbOjSjf NUhUkG SjOfG SjO dcd aj dcd hYdi dg hCUMGHg CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydj eMahX (B- (3HZOGO (B(195) s
Keywords: (3GdJhMjO hGdedd hGdfMds